Functional and Structural Responses of Arctic and Alpine Soil Prokaryotic and Fungal Communities Under Freeze-Thaw Cycles of Different Frequencies - Perez-Mon, Carla; Frey, Beat; Frossard, Aline (Frontiers in Microbiology, 2020)
Ongoing climate change involves increasing snow scarcity, which results in more frequent freeze-thaw cycles (FTCs) in polar and alpine soils. Although repeated FTCs have been shown to alter the structure and functions of soil microbial communities, a thorough understanding on the influence of FTCs frequency on polar and especially alpine soil microbiomes is still elusive. Here, we investigated the impact of repeated weekly vs. daily FTC frequencies on the structure and functions of prokaryotic and fungal communities from north- and south-exposed soils from two mountain ridges, one in the Arctic and one in the High-Alps. FTCs affected prokaryotic communities more strongly than fungal communities, where mainly cold-tolerant and opportunistic fungi (e.g. Mrakia, Mortierella) were responsive. Prokaryotic communities were more affected by weekly FTCs than by daily FTCs. Daily FTCs favored fast-growing bacteria (e.g. Arthrobacter), while oligotrophic and largely uncultured taxa (e.g. Verrucomicrobia) benefited from weekly FTCs. FTCs negatively affected microbial respiration but had minor impacts on C-, N- and P-acquiring enzymatic activities. Plausible pre-adaptation of the microbial communities to naturally occurring frequent FTCs at their site of origin did not show a clear influence on the microbial responses to the tested FTCs. Altogether, our study provides an integrative overview on potential structural and functional changes of soil microbial communities in polar and alpine regions in response to the projected increase in FTCs; therefore advancing our understanding on the impact of climate change in these rapidly changing ecosystems.